(untitled) (mathematica didactica, 2011)
Geometric modeling usually allows for two quite different approaches: dataoriented modeling starts with concrete measurements and moves bottom-up towards a general model while the top-down theory-driven approach is guided by established theorems in deriving a suitable model. Contrasting the two perspectives provides the opportunity to compare and juxtapose both approaches and to analyze them from a learners’ perspective.